Demographic Characteristics and Differential Item Functioning of Economics Achievement Test in Plateau State, Nigeria - Mawak, Joseph John; Mustapha, Abbas Y.; Wakjissa, Sayita S.G. (NIU Journal of Humanities, 2019)
The study investigated the demographic characteristics of students and differential item functioning of economics achievement test items for SSII students in Plateau State, Nigeria. The motivation of the study was the persistent poor performance of students in external examinations in the subject which could be attributed to the quality of test items used by teachers in assessing students’ achievement in the subject. Again, some of the test items used in assessing students function differentially based on students’ gender, school location and school type, which have resulted in students with the same ability performing differently. Furthermore, the teachers use the same test items to measure secondary issues above primary issues. Again there are no existing developed tests in economics in the study area that can be used in assessing students in the subject within the study area. The research design used for the study was instrumentation and cross-sectional survey research designs. The population of the study consisted of all the 23712 SS2 economics students in Plateau State whereby a sample of 1454 SSII students were selected and used for the study. Multistage sampling technique was used to ensure that adequate number of students were selected from each zone, local government, schools and students. A sample of 134 schools made up of 74 private schools and 60 public schools with 68 from rural and 66 from urban; 720 males and 734 females were used for the study. The instrument for data collection was an Economics Achievement Test (EAT) developed and calibrated by the researcher. One research question and three hypotheses were formulated to guide the study. The research question was answered using the Kaiser-Meyer Olkim (kmo) and scree plot while the hypotheses were tested using structural equation modelling of the IRTPRO. The validity of the instrument was established using a test blue print and experts’ judgments. The reliability of the instrument was estimated using Omega reliability procedure and coefficient of 0.83 was obtained for the EAT items. The results of the analysis revealed that some of the items functioned differently for the testees based on gender, school type and school location. It was recommended among others that teachers should determine the differential functioning of test items before using the tests for conducting continuous assessments on students. Keywords: Demographic characteristics, Differential item functioning.